KEBERAGAMAN KRITERIA BERBAGAI ORMAS DI INDONESIA DALAM MENENTUKAN HILAL - Ihsani, Ma’dinal (ELFALAKY: Jurnal Ilmu Falak, 2021)
Hilal is the visible crescent phenomenon that appears from the Earth's surface after the ijtima. The appearance of the hilal is inevitable  after the ijtima event of the Sun and Moon in one astronomical longitude at each end of the month toward the beginning of the month. This raises some perspectives among experts, whether the hilal is visible and can be seen or not. It is not uncommon controversy for each other because they have not found agreement in the interpretation of the hilal. In Indonesia, each Islamic mass organization has different ways of determining the hilal or what is often termed rukyatul hilal. Keyword: fiqh, NU, Muhammadiyyah, LDII, HTI, rukyat, hilal